Fibril Structure Demonstrates the Role of Iodine Labelling on a Pentapeptide Self‐Assembly. Issue 14 (17th February 2022) - Marchetti, Alessandro; Pizzi, Andrea; Bergamaschi, Greta; Demitri, Nicola; Stollberg, Ulrike; Diederichsen, Ulf; Pigliacelli, Claudia; Metrangolo, Pierangelo
Abstract: Iodination has long been employed as a successful labelling strategy to gain structural insights into proteins and other biomolecules via several techniques, including Small Angle X‐ray Scattering, Inductively Coupled Plasma Mass Spectrometer (ICP‐MS), and single‐crystal crystallography. However, when dealing with smaller biomolecular systems, interactions driven by iodine may significantly alter their self‐assembly behaviour. The engineering of amyloidogenic peptides for the development of ordered nanomaterials has greatly benefitted from this possibility. Still, to date, iodination has exclusively been applied to aromatic residues. In this work, an aliphatic bis‐iodinated amino acid was synthesized and included into a custom pentapeptide, which showed enhanced fibrillogenic behaviour. Peptide single crystal X‐ray structure and powder X‐ray diffraction on its dried water solution demonstrated the key role of iodine atoms in promoting intermolecular interactions that drive the peptide self‐assembly into amyloid fibrils. These findings enlarge the library of halogenated moieties available for directing and engineering the self‐assembly of amyloidogenic peptides. Abstract : Iodination is an attractive yet minimal functionalization to engineer the self‐assembly of amyloidogenic peptides. Despite having received little attention in the field, iodinated aliphatic residues can expand the library of functional moieties able to tune peptides self‐assembly. In our work, a custom iodinated aliphatic amino acid was synthesized and introduced into a pentapeptide, enhancing its self‐assembly and crystallogenic properties.